The Effectiveness of Routine Recitation Activities on Students’ Ability in Reading and Writing the Qur’an at State Junior High School 7 Buton Tengah - Pratiwi, Ani; Madi, Madi; Basri, Basri (Universitas Pahlawan Tuanku Tambusai, 2026)
The difficulties that students often experience in studying the Al-Qur'an, especially in class VIII E, became the impetus for conducting this research. Students at SMP Negeri 7 Buton Tengah have problems in terms of encouraging them to read the Al-Qur'an, feeling lazy, lacking self-confidence and accuracy in recognizing makhraj and tajwid. With regular Koran activities carried out every Wednesday or Friday, one way to make it easier for students to study the Koran, from the Iqro level to the Al-Qur'an level, is to use the talaqqi (musyafahah), talqin technique, and tikrar techniques. With this method, students read directly in front of the teacher, and the teacher immediately corrects if there are mistakes in makharj or tajwid and the teacher uses (talaqqi), even the teacher reads it first then the students imitate it (talqin), then the teacher reads the verses of the Koran again and the students imitate it (tikrar). The aim of this research is to ensure that students' reading is in accordance with correct Tajweed rules and good reading standards. This study uses a qualitative approach to understand and measure students' Quranic reading and writing abilities. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation as research instruments in addition to purposive sampling techniques (purposeful samples). The research findings show that class VIII E uses talaqqi, talqin, and tikrar techniques. From cycle I, when the average score was 65,80, to cycle II when the average score was 89,09, included in the very good category, students' understanding of Quranic reading and writing abilities has increased over the past year.